2010
DOI: 10.1021/cg100538z
|View full text |Cite
|
Sign up to set email alerts
|

Epitactically Interpenetrated High Quality ZnO Nanostructured Junctions on Microchips Grown by the Vapor−Liquid−Solid Method

Abstract: The usability of nanostructures in electrical devices such as gas sensors critically depends on the ability to form high quality contacts and junctions, at least in a two terminal setup. For the fabrication of various nanostructures, vapor-liquid-solid (VLS) growth is meanwhile a widely spread and very efficient technique for many semiconductors. However, as already demonstrated in the literature, forming contacts with the VLS grown structures to utilize them in a device is typically tedious. Either the substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…ZnO has attracted intensive research effort for its unique properties and versatile applications in transparent electronics, chemical sensors, and spin electronics [2][3][4][5][6][7][8]. A variety of metal oxides like zinc oxide, titanium dioxide (TiO 2 ), and silicon dioxide (SiO 2 ) and different techniques such as chemical coprecipitation [9,10], sol-gel process [11,12] chemical vapour deposition [13], thermal decomposition [14,15], hydrothermal synthesis [16,17], solidstate reaction [18], spray pyrolysis [19], vapour-liquid-solid method [20], and microemulsion precipitation [21][22][23] have been used so far. Hingorani et al also reported the synthesis of ZnO nanoparticles (NPs) and it was the first study using reverse microemulsion in the early 1990s [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO has attracted intensive research effort for its unique properties and versatile applications in transparent electronics, chemical sensors, and spin electronics [2][3][4][5][6][7][8]. A variety of metal oxides like zinc oxide, titanium dioxide (TiO 2 ), and silicon dioxide (SiO 2 ) and different techniques such as chemical coprecipitation [9,10], sol-gel process [11,12] chemical vapour deposition [13], thermal decomposition [14,15], hydrothermal synthesis [16,17], solidstate reaction [18], spray pyrolysis [19], vapour-liquid-solid method [20], and microemulsion precipitation [21][22][23] have been used so far. Hingorani et al also reported the synthesis of ZnO nanoparticles (NPs) and it was the first study using reverse microemulsion in the early 1990s [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…When the diameter of gold NPs is relatively small, growth of ZnO nanorods occurs (Figure 1(a)) with NPs on the top; however, if the particle diameter is large enough formation of nanoSail type structures takes place as shown in Figures 1(b) to 1(d) with increasing order of magnifications. For instance, fabrication details of nanorods and nanoSails are described in our previous works [11,23] whereas the corresponding electron microscopy images are shown in Figure 1.…”
Section: Vls and Modified Vls Approachesmentioning
confidence: 99%
“…However, it is more effective to perform direct fabrication of nanowires between the contacts on microstructured Si-chips. Various methods such as templates [3][4][5], solution growths [6], lithographic methods (electron beam and conventional) [7,8], vapor-liquid-solid (VLS) and its modified versions [9][10][11], and several others have been employed to synthesize 1D structures. Many of these methods stated earlier are either too slow or too expensive when one looks from mass fabrication or market point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other 1D nanomaterials, ZnO has three prominent advantages: first, it is a semiconductor with a piezoelectric effect, which is the basis for electric mechanical coupling sensors and inverters; second, the biosecurity and biocompatibility of ZnO is relatively high, so it can be used in medicine; third, ZnO has the largest range of known nanostructures, including nanowires [2][3][4][5][6], nanorods [7][8][9], nanobelts [10][11][12][13], nanotubes [14][15][16], nanoplates [28][29][30], nanospheres [31], nanotrees [32], nanoleaves [33], and nanosails [34]. In addition, ZnO tetrapod [35], microrod/microwire [36,37], porous array [38], matrix [39], and 3D network nanostructure [20,40] have been obtained.…”
Section: Introductionmentioning
confidence: 99%